2016
DOI: 10.1213/ane.0000000000001562
|View full text |Cite
|
Sign up to set email alerts
|

Neuraxial Anesthesia Reduces Lymphatic Flow: Proof-of-Concept in First In-Human Study

Abstract: Dilation of lymphatic vessels may contribute to iatrogenic dissemination of cancer cells during surgery. We sought to determine whether neuraxial anesthesia reduces regional lymphatic flow. Using nuclear lymphoscintigraphy, 5 participants receiving spinal anesthesia for brachytherapy had lower extremity lymph flow at rest compared with flow under conditions of spinal anesthesia. Six limbs were analyzed. Four limbs were excluded because of failure to demonstrate lymph flow (1 patient, 2 limbs), colloid injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Activation of β-adrenoceptor signalling promotes remodelling of the tumour-associated lymphatic and blood vasculature through inflammation-dependent mechanisms 67,68,70 . Furthermore, the sympathetic nervous system also regulates lymphatic flow through innervation of lymphangions, the structural contractile elements that surround lymphatic vessels and regulate the flow rate of lymphatic fluid 34,80,81 . Increased circulating catecholamine levels have been shown to accelerate flow through the lymphatic vessels that drain the primary tumour, thereby promoting the dissemination of tumour cells in vivo 68 .…”
Section: Activation Of Neural Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of β-adrenoceptor signalling promotes remodelling of the tumour-associated lymphatic and blood vasculature through inflammation-dependent mechanisms 67,68,70 . Furthermore, the sympathetic nervous system also regulates lymphatic flow through innervation of lymphangions, the structural contractile elements that surround lymphatic vessels and regulate the flow rate of lymphatic fluid 34,80,81 . Increased circulating catecholamine levels have been shown to accelerate flow through the lymphatic vessels that drain the primary tumour, thereby promoting the dissemination of tumour cells in vivo 68 .…”
Section: Activation Of Neural Signallingmentioning
confidence: 99%
“…Neuraxial anaesthesia, used in addition or as an alternative to general anaesthesia, reduces circulating catecholamine levels, inflammation, immunosuppression, and provides an alternative means of achieving sympathetic blockade during cancer surgery 82 , inflammation, and immunosuppression [118][119][120] . Furthermore, the findings of a study published in 2016 indicate that perioperative lymph flow is inhibited by use of neuraxial anaesthesia 81 , a phenomenon that has also been documented in animal models 121 . This observation raises the intriguing possibility that a potential anticancer effect of neuraxial anaesthesia might result from a reduction in the extent of dissemination of residual cancer cells from a surgical wound.…”
mentioning
confidence: 91%
“…[10] Similarly, Childers et al [17] found that the use of β-blockers significantly reduced risk of breast cancer recurrence and breast cancer death in their meta-analysis. On the other hand, Hiller et al [18] reported that spinal anesthesia reduces lymphatic flow (in lymphatic vessels and nodes) through a likely mechanism of sympathectomy in patients with cervical and prostate cancer for brachytherapy. In their studies, accumulation of radioisotope-labeled colloid was decreased in inguinal lymph nodes and lymphatic vessels after spinal anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Local anesthetics and regional anesthesia effects on lymph function have been evaluated in a few studies. In human subjects, 42 lymphoscintigrams using technetium-99m antimony sulfide colloid were performed during control conditions and after subjects received a spinal anesthetic composed of ropivacaine (25 mg) and clonidine (22.5 μg). Tracer material was injected subdermally into the first web space of both feet.…”
Section: Anesthetics Inhibit Lymphatic Functionmentioning
confidence: 99%